Bacterial Cellulose From Rice Waste Water With Addition Chitosan, Glycerol, And Silver Nanoparticle - Eli Rohaeti; Endang WLFX; Anna Rakhmawati (Universitas Jenderal Soedirman, 2016)
This study aimed to prepare silver nanoparticles chemically, deposite silver nanoparticles on bacterial cellulose-chitosan-glycerol composite based rice waste water, as well as test the antibacterial activity of bacterial cellulose and its composite. Preparation of silver nanoparticles was conducted by chemical reduction of silver nitrate solution, as well as trisodium citrate as the reductor. Bacterial cellulose from rice waste water is fermented by the bacteria Acetobacter xylinum for 7 days. The dried bacterial cellulose was composited with chitosan and glycerol by immersion method on 2% of chitosan solution and 0.5% of glycerol solution. UV-Vis spectroscopy is used to determine the formation of silvernanoparticles and Particle Size Analyzer to test the size and particle size distribution. Characterization was conducted to bacterial cellulose and its composite included functional groups by FTIR, the mechanical properties by Tensile Tester, crystallinity by XRD, surface photograph by SEM, and antibacterial test against S. aureus and E. coli by the shake flask turbidimetry method. Silver nanoparticle characterization indicated that silver nanoparticles are formed at a wavelength of 421.80 nm, yellow, diameter particle size of 61.8 nm. SEM images showed that the surface of bacterial cellulose had deposited silver nanoparticles and antibacterial test showed an inhibitory effect of bacterial cellulose, bacterial cellulose-chitosan composite, and bacterial cellulose-chitosan-glycerol composite which are deposited silver nanoparticles against the growth of S. aureus and E. coli bacteria.